504. Change in Clostridium difficile Strain-Type Distribution After Implementation of Diagnostic Stewardship. (26th November 2018) - McMillen, Tracy; Chow, Hoi Yan; Aslam, Anoshé; Brite, Jennifer; Babady, N Esther; Kamboj, Mini
Abstract: Background: The aim of this study was to evaluate the change in strain-type distribution after eliminating testing of formed and laxative induced diarrheal stool. Methods: Beginning in July 2013, all Clostridium difficile -positive stool samples by Cepheid's GeneXpert were routinely typed using Multi-Locus Sequence Typing (MLST). MLST was performed as previously described (1). After implementation of rejection policy and re-education of staff, strain type (ST) distribution among tested samples were analyzed and compared with historic data. Results: After evaluation of our historical typing data the 10 most frequent ST were identified. Diagnostic stewardship led to 40.0% reduction in testing volume, the positivity rate increased from 12.0% to 12.6%. The frequency distribution of threemost prevalent strain types (MLST-2, 8, and 42) declined by 38%, 60%, and 42%, respectively. The absolute number of epidemic strains, ST-1 and ST-11, remained unchanged and the frequency distribution increased from 9.6% to 14.0%. No clonal outbreaks were detected during this time. Conclusion: Implementation of diagnostic stewardship led to a reduction in recovery of endemic strains without substantial impact on detection of hypervirulent or epidemic strains. Disclosures: All authors: No reported disclosures.